Relevance of scope management and organizational change management in IT deployment projects - Antikainen, Jani (2010)
This research investigates the relevance of project scope management and organizational change management in the context of IT deployment projects in which new IT artifacts are introduced in organizations. Scope management refers to the management of project content, whereas organizational change management refers to communicating, justifying and leading the change delivered by the project to the organization receiving the new IT artifacts. Deployment refers to the process of “taking the artifacts into use”, involving both emergent and planned changes. This research provides new insights for both aspiring and current deployment project managers who need to understand better the characteristics of deployment projects, the motivations of project managers, and the most important success factors of deployment projects as those differ from software development projects and from other types of projects.